Improving the Precision of Calibrating a Large Low-background Proportional Counter. (December 2020) - Petrenko, O D; Gangapshev, A M; Gavrilyuk, Yu M; Kazalov, V V; Kuzminov, V V; Panasenko, S I; Ratkevich, S S; Tekueva, D A
Abstract: The study of low-yield effects requires not only good quality of the original data but also puts high requirements for their processing procedures to increase the efficiency of the selection of useful events. The exploiting of the large cylindrical proportional counter's electrostatic topology allows improving the extrapolation of information about the primary ionization of a multipoint event. Long-term calibration measurements with an external 109 Cd-source allowed the development of a new method for analyzing the pulse shape from a sizeable proportional counter. Optimized analysis of the current's pulse shape from the electron cloud of primary ionization in the counter improved the resolution and energy calibration. As a result, the efficiency of selecting useful events was increased by 25%.